Regeneration in the Auditory Organ in Cuban and African Dwarf Crocodiles (Crocodylus rhombifer and Osteolaemus tetraspis) Can We Learn From the Crocodile How to Restore Our Hearing? - Li, Hao; Staxäng, Karin; Hodik, Monika; Melkersson, Karl-Gunnar; Rask-Andersen, Mathias; Rask-Andersen, Helge (Frontiers in Cell and Developmental Biology, 2022)
Background: In several non-mammalian species, auditory receptors undergo cell renewal after damage. This has raised hope of finding new options to treat human sensorineural deafness. Uncertainty remains as to the triggering mechanisms and whether hair cells are regenerated even under normal conditions. In the present investigation, we explored the auditory organ in the crocodile to validate possible ongoing natural hair cell regeneration. Material and Methods: Two male Cuban crocodiles (Crocodylus rhombifer) and an adult male African Dwarf crocodile (Osteolaemus tetraspis) were analyzed using transmission electron microscopy and immunohistochemistry using confocal microscopy. The crocodile ears were fixed in formaldehyde and glutaraldehyde and underwent micro-computed tomography (micro-CT) and 3D reconstruction. The temporal bones were drilled out and decalcified. Results: The crocodile papilla basilaris contained tall (inner) and short (outer) hair cells surrounded by a mosaic of tightly connected supporting cells coupled with gap junctions. Afferent neurons with and without ribbon synapses innervated both hair cell types. Supporting cells occasionally showed signs of trans-differentiation into hair cells. They expressed the MAFA and SOX2 transcription factors. Supporting cells contained organelles that may transfer genetic information between cells, including the efferent nerve fibers during the regeneration process. The tectorial membrane showed signs of being replenished and its architecture being sculpted by extracellular exosome-like proteolysis. Discussion: Crocodilians seem to produce new hair cells during their life span from a range of supporting cells. Imposing efferent nerve fibers may play a role in regeneration and re-innervation of the auditory receptors, possibly triggered by apoptotic signals from wasted hair cells. Intercellular signaling may be accomplished by elaborate gap junction and organelle systems, including neural emperipolesis. Crocodilians seem to restore and sculpt their tectorial membranes throughout their lives.